Algorithms and Computation 23rd International Symposium, ISAAC 2012, Taipei, Taiwan, December 19-21, 2012. Proceedings - Chao, Kun-Mao.; Hsu, Tsan-sheng.; Lee, Der-Tsai.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 23rd International Symposium on Algorithms and Computation, ISAAC 2012, held in Taipei, Taiwan, in December 2012. The 68 revised full papers presented together with three invited talks were carefully reviewed and selected from 174 submissions for inclusion in the book. This volume contains topics such as graph algorithms; online and streaming algorithms; combinatorial optimization; computational complexity; computational geometry; string algorithms; approximation algorithms; graph drawing; data structures; randomized algorithms; and algorithmic game theory.
Graph algorithms -- online and streaming algorithms -- combinatorial optimization -- computational complexity -- computational geometry -- string algorithms -- approximation algorithms -- graph drawing -- data structures -- randomized algorithms -- algorithmic game theory.
Keywords: Computer science; Computer Communication Networks; Data structures (Computer science).; Computer software; Electronic data processing; Computational complexity; Computer graphics; Computer Science; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science; Computer Communication Networks; Computer Graphics; Data Structures; Numeric Computing